2016
DOI: 10.1111/and.12701
|View full text |Cite
|
Sign up to set email alerts
|

Sperm with fibrous sheath dysplasia and anomalies in head-neck junction: focus on centriole and centrin 1

Abstract: Spermatozoa with a rare combination of two monomorphic sperm defects, dysplasia of the fibrous sheath (DFS) and alterations in head-mid-piece junction were analysed. The main focus was to explore the status of the centriole, a key organisation during fertilisation, using the centrin 1, a calcium-binding protein linked to this structure. The sperm quality was examined by light, scanning and transmission electron microscopy (SEM, TEM); immunocytochemistry was performed for tubulin, A-kinase anchor protein 4 (AKA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Microscopy of dysplastic sperm reveals an increased and disorganized fibrous sheath with disruption of the underlying axoneme (Chemes et al, 1987a). Immunofluorescence with the centriolar protein Centrin-1 shows frequent abnormal positioning of the centrioles, sometimes with duplication, resulting in two nucleus-implantation sites (Moretti et al, 2017). Initial attempts at ICSI with dysplastic sperm were unsuccessful at achieving pregnancy, due to failure of either fertilization or embryo development (Chemes and Rawe, 2003).…”
Section: Epidemiological Evidence For Centriole Contribution To Humanmentioning
confidence: 99%
“…Microscopy of dysplastic sperm reveals an increased and disorganized fibrous sheath with disruption of the underlying axoneme (Chemes et al, 1987a). Immunofluorescence with the centriolar protein Centrin-1 shows frequent abnormal positioning of the centrioles, sometimes with duplication, resulting in two nucleus-implantation sites (Moretti et al, 2017). Initial attempts at ICSI with dysplastic sperm were unsuccessful at achieving pregnancy, due to failure of either fertilization or embryo development (Chemes and Rawe, 2003).…”
Section: Epidemiological Evidence For Centriole Contribution To Humanmentioning
confidence: 99%
“…Dysfunctional sperm centrioles were viewed as one trigger for the development of acephalic spermatozoa . Moretti et al proved that abnormal expression of centrin 1, one of centriole protein, may take part in fibrous sheath dysplasia, anomalies in head‐neck junction and globozoospermia . Our previous work has shown that homozygous mutation in centrosomal protein 135 (CEP135) may associate with multiple morphological abnormalities of the sperm flagella .…”
Section: Introductionmentioning
confidence: 97%
“…19 Moretti et al proved that abnormal expression of centrin 1, one of centriole protein, may take part in fibrous sheath dysplasia, anomalies in head-neck junction and globozoospermia. 20,21 Our previous work has shown that homozygous mutation in centrosomal protein 135 (CEP135) may associate with multiple morphological abnormalities of the sperm flagella. 22 All of these studies suggest that CEPs play an important role in maintaining normal sperm morphology and function.…”
mentioning
confidence: 99%
“…It is mainly ascribed to flagella abnormalities, leading to sperm immotility (Gunes et al, 2018). Transmission electron microscopy (TEM) analysis has documented a number of ultrastructural defects at the sperm level, such as dynein arm deficiency (Kordus et al, 2008), abnormal connecting pieces, shortened mid pieces with attenuated mitochondria sheaths, poorly developed annulus, abnormal outer dense fibers, axonema missing the two central microtubules (Yokota et al, 1993;McLachlan et al, 2012), or dysplasia of the fibrous sheath (Moretti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%